Humoral responses to the CoronoVac vaccine in healthcare workers - Gokhan Eyupoglu; Ramazan Guven; Nuran Karabulut; Adem Cakir; Kemal Sener; Burcu Genc Yavuz; Davut Tekyol; Akkan Avci (Revista da Sociedade Brasileira de Medicina Tropical, 2023)
ABSTRACT Background: This study aimed to assess the immunoglobulin G (IgG) antibody response rate in emergency department (ED) healthcare workers (HCWs) and potential adverse effects after CoronaVac vaccination. Methods: All included HCWs were grouped based on the previous history of coronavirus disease 2019 (COVID-19) and the number of vaccinations. Furthermore, the IgG antibody response was evaluated based on the sex and smoking status of HCWs. Those with a cut-off index of ≥1.00 after vaccination with CoronaVac were considered to have had COVID-19 and had an adequate humoral response. Results: Among 224 ED HCWs, 18% experienced the adverse effects of CoronaVac vaccine, the most prevalent being pain in the injection site. The IgG antibody response rate was 20% after the first dose of vaccine, while the response rate increased to 90% after the second dose. Female HCWs had higher IgG response rates compared with male HCWs (53.8 [15.9-147.0] vs 31.2 [4.5-124.0]). Non-smokers had higher IgG response rate compared with smokers (49.0 [11.5-160.5] vs 23.1 [7.4-98.5]). Conclusion: A single dose of CoronaVac does not produce a sufficient antibody response; hence, two doses are recommended. Men have a lower IgG response compared with women. Smokers had a lower IgG response rate compared with non-smokers. Therefore, it may be necessary to carefully assess the humoral responses of men and smokers when implementing a community vaccination program.